Carotenoids and Human Health - Amengual, Jaume (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Carotenoids are a group of approximately 600 compounds synthesized by photosynthetic organisms. These pigments are abundant in fruits and vegetables, as well as in certain animal products such as eggs and salmon, being responsible for their colorful appearance. The bioactive properties of certain carotenoids in human health are clear, as some of these compounds have antioxidant properties and serve as the only precursors of vitamin A in nature. The aim of this Special Issue entitled "Carotenoids and Human Health" is to provide the scientific community with an updated perspective of this exciting and growing research area. We compiled 19 papers from some of the most prominent scientists in the carotenoid field, including seven literature reviews and 12 original publication, covering topics such as cancer, obesity, vision, cognitive function, and skin health.